Eagle’s Syndrome: An Unusual cause of throat pain-Case Study - Maha Khalil, Arshad Ullah Afridi, Muhammad Saeed Gohar, HASSAN, HARIS, SAANA (Pakistan Journal of Medical & Health Sciences, 2022)
Eagle’s syndrome or styalgia is characterised by the anatomical bone deformity of the styloid process, as identified by Wat W. Eagle in 19491. An aggregate of symptoms caused by the elongation and severe calcification of the temporal bone’s styloid process, as well as calcification of the ligaments attached to this process, including the styloid and stylomandibular ligaments, have been identified2. The styloid process is typically 20 to 30 mm in length, and patients with elongated styloid processes of 40 mm or longer have clinical distress 1,3 . This styloid process elongation could be unilateral or bilateral 4. It affects around 4% of the general population, with 3:1 female predominance, however only 4% of these people experience associated symptoms 3. Eagle mainly characterized two syndromes: “classic styloid syndrome” following tonsillectomy, and “stylocarotid syndrome” unrelated to tonsillectomy6. The “styloidogenic jugular compression syndrome”, a third variation of Eagle syndrome, was recently identified, in which the jugular vein is squeezed, resulting in cerebral venous hypertension and, most commonly, headaches1.